Electrode Material Optimization of Nitrous Oxide Recovery from Incineration Leachate in a ΔnosZ Pseudomonas aeruginosa/MEC System - Yong Liu; Bing Yan; Song Xia; Shuanglin Gui; Haiwei Jiang; Hanbing Nie; Dezhi Sun (Fermentation, 2023)
Nitrous oxide (N2O) is not only recognized as a potent greenhouse gas, but it is also used in industry as a clean energy source. In this study, different electrode materials of carbon felt and graphite were equipped in the ΔnosZ P. aeruginosa/microbial electrolysis cell (MEC) systems to explore the optimization mechanism for long-term N2O recovery during incineration leachate treatment. The carbon felt group showed a better performance in N2O recovery across 45 days of operation. The N2O conversion efficiency was above 80% and the proportion of N2O in biogas accounted for 80.6% in the carbon felt group. qRT-PCR analysis was conducted to evaluate the expression of genes involved in denitrification (norB) and electroactivity (phzG, phzM, and phzH) of ΔnosZ P. aeruginosa. The results showed a significant upregulation in the suspended biomass (day 21) and the electron-attached biomass (day 45) from the carbon felt-equipped reactor, which was highly related to the opportunity of biomass exposed to the phenazine derivatives. By the carbon felt optimization in the system, 82.6% of the Pseudomonas genus survived after 45 days of operation. These results indicate that the carbon felt electrode has a more sustainable performance for N2O recovery in the ΔnosZ P. aeruginosa/MEC system.